Potential Pathway of Nitrous Oxide Formation in Plants - Timilsina, Arbindra; Zhang, Chuang; Pandey, Bikram; Bizimana, Fiston; Dong, Wenxu; Hu, Chunsheng (Frontiers in Plant Science, 2020)
Plants can produce and emit nitrous oxide (N2O), a potent greenhouse gas, into the atmosphere, and several field-based studies have concluded that these emissions are substantial. However, the exact mechanisms of N2O production in plant cells are unknown. Many studies have hypothesized that plants might act as a medium, transporting the N2O produced by soil inhabiting micro-organisms. However, aseptically grown plants and axenic algal cells supplied with nitrate (NO3) are reported to emit N2O, indicating that it is produced inside the plant cells by some physiological phenomena. In this study, the possible sites, mechanisms, and enzymes involved in N2O production in plant cells are discussed. Based on the experimental evidence from various studies, we have determined that N2O can be produced from nitric oxide (NO) in the mitochondria of plants. NO is a signaling molecule at the cellular level and is produced through oxidative and reductive pathways in every eukaryotic cell. During hypoxia and anoxia, the processing of NO3 in the cytosol produces nitrite (NO2) and the NO2 is reduced to form NO along reductive pathway in mitochondria. Under low oxygen condition, the NO formed in the mitochondria can be further reduced to N2O by the reduced form of cytochrome c oxidase (CcO). So, this pathway is active only when the cell experiences hypoxia or anoxia, and may be responsible for N2O formation in plants and soil-dwelling animals, as reported by a number of previous studies. NO can be toxic at higher concentration, so the reduction of NO to N2O in the mitochondria might protect the integrity of the mitochondria and protect the cell from the toxicity of NO accumulation during hypoxia and anoxia, and it should be a matter of further research. As NO3 is a major source of nitrogen for plants, and all plants may experience hypoxic and anoxic conditions owing to soil environmental factors, a significant global biogenic source of N2O may be its formation in plants via this proposed pathway.